2000
DOI: 10.1093/ndt/15.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Early echocardiographic changes and survival following renal transplantation

Abstract: In this Preliminary Report, we conclude that echocardiographic parameters are associated with adverse outcome in patients receiving renal replacement therapy (RRT). Different echocardiographic parameters are associated with adverse outcome before and after renal transplantation and improvement of pre-transplant abnormalities (e.g. poor LV systolic function) following transplantation does not necessarily confer survival benefits. Whether this is a genuine observation or a reflection of the interpretation of ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 20 publications
1
47
5
Order By: Relevance
“…By and large these studies have shown that LV mass decreases posttransplantation and that this decrease parallels posttransplant improvement in BP control (8 -18). Two studies have suggested that pretransplant LVH is predictive of posttransplant mortality in the first 5 yr, but none have had sufficient power and long enough follow-up to examine whether posttransplant persistence or development of LVH are predictive of death and cardiovascular events (21,22). We have previously shown that CHF appears to be more frequent in RTR than in the general population and is independently associated with a twofold increased risk of death.…”
Section: Discussionmentioning
confidence: 98%
“…By and large these studies have shown that LV mass decreases posttransplantation and that this decrease parallels posttransplant improvement in BP control (8 -18). Two studies have suggested that pretransplant LVH is predictive of posttransplant mortality in the first 5 yr, but none have had sufficient power and long enough follow-up to examine whether posttransplant persistence or development of LVH are predictive of death and cardiovascular events (21,22). We have previously shown that CHF appears to be more frequent in RTR than in the general population and is independently associated with a twofold increased risk of death.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, there was an increase in LVEF and reduction of cavity volumes after transplantation 19,21 , even in the pediatric population 23 . Moreover, Rakhit et al 29 , during a median follow-up of 4.2 years after kidney transplantation showed significant reduction in LVESVi of 33 ml/m 2 to 23 ml/m 2 .…”
Section: Discussionmentioning
confidence: 92%
“…McGregor et al 19 evaluated 67 patients four months after kidney transplantation and showed no impact on ventricular mass, and Patel et al 20 , in a cross-sectional study, also showed no difference in LV mass measured by magnetic resonance imaging in transplanted 21,22 , even in the pediatric population 23 .…”
Section: Discussionmentioning
confidence: 96%
“…LVH is associated with increased mortality on hemodialysis (736) and peritoneal dialysis (738). Although LVH often improves after renal transplantation (739)(740)(741)(742), it nevertheless predicts a worse posttransplant outcome (741,742). Even in the absence of randomized controlled trials it is reasonable to conclude that correcting LVH in hemodialysis patients may reduce risk and improve outcomes while on the waiting list and after renal transplantation.…”
Section: Recommendationsmentioning
confidence: 99%
“…Severe, irreversible heart failure should probably preclude renal transplantation unless heart transplantation is also considered. However, many patients with mild or moderate (idiopathic) cardiac dysfunction may respond to renal transplantation with an improvement in myocardial function (742,(757)(758)(759)(760)(761)(762)(763)(764)(765). Indeed, most investigators have reported that echocardiographic or radionuclide-determined ejection fraction increases and left ventricular mass decreases after renal transplantation.…”
Section: Recommendationsmentioning
confidence: 99%